2018
DOI: 10.1002/jez.2242
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor kinematics of tree squirrels (Sciurus carolinensis) in free‐ranging and laboratory environments: Implications for primate locomotion and evolution

Abstract: The grasping capabilities and gait kinematics characteristic of primates are often argued to be adaptations for safely moving on small terminal branches. The goal of this study was to identify whether Eastern gray squirrels (Sciurus carolinensis) -arboreal rodents that frequently move and forage on small branches, lack primate-like grasping and gait patterns, and arguably represent extant analogs of a stem primate ancestor -adjust gait kinematics to narrow and non-horizontal branches. We studied locomotor kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 84 publications
5
25
0
Order By: Relevance
“…Finally, we found that free‐ranging Callitrichinae primarily used asymmetrical running gaits. Asymmetrical gaits permit the two limbs of a girdle to work in concert to grasp substrates and are frequently used by other small‐bodied arboreal mammals (Dunham et al, ; Lammers & Zurcher, ; Schmidt, ; Shapiro, Kemp, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we found that free‐ranging Callitrichinae primarily used asymmetrical running gaits. Asymmetrical gaits permit the two limbs of a girdle to work in concert to grasp substrates and are frequently used by other small‐bodied arboreal mammals (Dunham et al, ; Lammers & Zurcher, ; Schmidt, ; Shapiro, Kemp, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…We used modified GoPro Hero 5 cameras (GoPro, Inc., San Mateo, CA) equipped with a Back‐Bone Ribcage H5Pro (Back‐Bone, Ottawa, Ontario, Canada) and C mount Fujinon HD 8–80 mm Vari‐Focal CCTV lenses (Fujifilm, Tokyo, Japan) (Dunham et al, ). We filmed at 1080 p resolution and 120 fps which provided a sufficient footage for recording limb touchdown and liftoff events (Dunham et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers studying locomotion in both field and laboratory contexts have called for increased efforts in integrating research methods and theoretical frameworks to expand our understanding of primate gait plasticity and the relationship between gait and ecology (Bezanson, ; D'Août & Vereecke, ; Nyakatura & Heymann, ; Stevens & Carlson, ). Bringing laboratory methods to the field (including high‐speed video and the collection of 3D kinematic data) is now realistic given technological advances (Dunham et al, ; Dunham et al, ; Guillot, ; Shapiro et al, ; Thompson et al, ; Youlatos & Gasc, ). Therefore, primatologists now have the opportunity to precisely measure locomotor behaviors in natural habitats, and future research will further our understanding of the evolution of complex locomotor behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of primate gait across complex substrates in the laboratory as well as in the wild is necessary to fully understand kinematic adjustments in response to environmental factors. Now that laboratory methods can be effectively implemented in field settings (Blanchard & Crompton, ; Cheyne, ; Dunbar & Badam, ; Dunham et al, ; Dunham et al, ; Guillot, ; Isler & Thorpe, ; Nyakatura & Heymann, ; Shapiro et al, ; Stevens, Ratsimbazafy, & Ralainasolo, ; Youlatos & Gasc, ), there is great potential for assessing adaptations to the substantial substrate variability that exists in the wild.…”
Section: Introductionmentioning
confidence: 99%